Effect of post-harvest treatment on bioactive phytochemicals of Thai black rice - Orranuch Norkaew (2018)
© 2016 Elsevier Ltd Because black rice is rich in antioxidants, appropriate methods of post-harvest treatment are necessary for maintaining these bioactive phytochemicals. Drying methods, storage temperatures, storage duration, and packaging methods affected the contents of some bioactive compounds in the two varieties of Thai black rice used in this research. Sun drying reduces the loss of anthocyanins and γ-oryzanols more than does hot air drying. Glutinous black rice stored as paddy at cool room temperature retains more anthocyanins, γ-oryzanols, and vitamin E than does paddy stored at room temperature. Nylon/LLDPE pouches containing N 2 are the most suitable packaging for preserving the key aroma compound 2-acetyl-1-pyrroline (2AP), total phenolic, and anthocyanin contents of unpolished aromatic black rice. These pouches also retard the formation of some common off-flavor compounds.